Improved quantification method of crocins in saffron extract using HPLC-DAD after qualification by HPLC-DAD-MS. (15th November 2021) - Suchareau, Marlène; Bordes, Alexandra; Lemée, Laurent
Highlights: Trans 4-GG crocins was partially hydrolyzed into trans -2-G and cis -2-G crocins. Free crocetin resulted from crocins hydrolysis during storage at 60 °C. Trans-4-GG crocin was totally degraded when stored at 60 °C exposed to the light. k corrected with the molecular weight was accurate for adulterated saffron. 10 crocins were identified in saffron extracts using HPLC-DAD-MS. Abstract: Crocins in commercial liquid saffron extracts (Saffr'activ®) were identified using high-performance liquid chromatography (HPLC) with a diode array detector (DAD) and mass spectrometry (MS). The impact of storage on the qualities of the saffron extract were studied with HPLC-DAD-MS by exposing trans -4-GG crocin to environmental factors. Light and temperature induced degradation after only one week. Trans -4-GG crocin was totally hydrolyzed when stored at 60 °C and exposed to light. A quick and reliable method using HPLC-DAD was then developed to improve quantification of crocins in commercial liquid saffron extracts. An internal standard quantification method that uses a response factor, corrected with the molecular weight of each crocin, improved results for old saffron extracts.